Emerging Powers and Emerging Trends in Global Governance - Matthew D. Stephen (Global Governance, 2017)
In the 1990s, liberal optimism permeated the study and practice of international politics. International institutions were strengthened and the discourse and practice of global governance consolidated as a new approach to world affairs. Today, new powers are emerging in this institutionalized order. New powers have changed the power relations that underpinned global governance and are also economically, politically, and culturally different from established powers. Against this backdrop, this article investigates the impacts emerging powers are having on global governance. It presents six major trends and outlines their implications for the new global governance currently taking shape. Because new powers are emerging in an already institutionalized order, the emerging global governance order is gradually growing out of the existing one. Emerging powers are rendering parts of global governance dysfunctional, layering onto it, complicating it, but not overthrowing it.
Additional information: Zugl.: Accepted Manuscript (Postprint) von Stephen, Matthew D. (2021): Emerging Powers and Emerging Trends in Global Governance, in: Kurt Mills and Kendall Stiles (Eds.), Understanding Global Cooperation. Twenty-Five Years of Research on Global Governance, ISBN 978-90-04-46260-1, Brill, Leiden, Niederlande, 2021, pp. 445-465, doi: 10.1163/9789004462601_025.; More recent version: doi:10.1163/9789004462601_025
Keywords: 330; BRICS; emerging powers; fragmentation; global governance; international institutions; international politics